Seismic capacity of steel frames braced with cross-concentric rectangular plates: Non-linear analyses. (October 2019) - Trutalli, Davide; De Stefani, Lorenzo; Marchi, Luca; Scotta, Roberto
Abstract: The use of cross-concentric braced steel frames is still an effective way to realize earthquake-resistant buildings, thanks to the simplicity in the design and realization, assuring good strength, stiffness and ductility, provided that capacity design be fulfilled. Results from non-linear static and dynamic analyses of steel frames braced with cross-concentric rectangular plates are presented to discuss some significant design aspects that play a key-role in the definition of the hysteretic dissipative response of such structures. Parametric cyclic analyses were performed to assess the peak- and post-buckling lateral strength and the dissipative capacity of a small- and a full-scale frame, varying the non-dimensional slenderness of the bracing plates. Then, results of incremental dynamic analyses of a one-, three-, six- and ten-storey building are discussed to evaluate the behaviour factor for this structural typology, as function of inter-storey drift. Results from the parametric and incremental analyses give the optimal range of non-dimensional slenderness of the bracing plates as a compromise between limited overstrength and good dissipative capacity and confirm the behaviour factor currently provided by Eurocode, relating it with an expected inter-storey lateral drift. Highlights: Cross-concentric braced steel frames with bracing rectangular plates are studied. Non-linear FE model of X-CBF is validated against available test results. The effects of non-dimensional slenderness are examined with parametric analyses. Incremental dynamic analyses are performed to evaluate the behaviour factor. The value of behaviour factor is correlated with the inter-storey lateral drift.